Do Interictal Rates Influence Treatment Outcomes in Temporal Lobe Epilepsy?. Issue 2 (March 2020) - King-Stephens, David
Quantitative Electrocorticographic Biomarkers of Clinical Outcomes in Mesial Temporal Lobe Epileptic Patients Treated With the RNS System Desai N, Tchen T, Morrell MJ. Clinical Neurophysiology. 2019;130:1364-1374. doi:10.1016/j.clinph.2019.05.017 . OBJECTIVES: Find interictal electrocorticographic (ECoG) biomarkers of clinical outcomes in mesiotemporal lobe (MTL) epilepsy patients. METHODS: In the NeuroPace RNS System clinical trials with 256 patients, 20 MTL patients with the most reduction in clinical seizures at year 7 compared to baseline (upper response quartile: 96.5% median change) and 20 with the least reduction in clinical seizures (lower response quartile: 17.4% median change) were evaluated. Clinical and interictal ECoG features from the 2 response quartiles were compared. RESULTS: Demographic and clinical features were similar in the upper and lower response quartiles. Interictal spike rate (ISR) was substantially lower ( P < .0001) in the upper quartile patients, while normalized θ (4-8 Hz) and normalized γ (>25 Hz) were also different ( P < .05) between the 2 response quartiles. Interictal spike rate was positively correlated ( P < .05) with clinical seizure rates in 71% of the channels analyzed. Electrocorticographic records captured during months with no clinical seizures had the lowest ISR. CONCLUSIONS: Interictal spike rate is a strong differentiator of clinical response in MTL patients. Normalized θ and γ also differentiates clinical response. SIGNIFICANCE: In MTL patients, the ISR along with spectral power computed from chronic ambulatory baseline ECoGs may serve as biomarkers of clinical outcomes and maybe used as treatment end points.